A Fluorescence-Based Flippase Assay to Monitor Lipid Transport by Drs2-Cdc50 - Inja Van Der Linden; Sara Herrera; Cédric Montigny; Guillaume Lenoir; Thomas Pomorski; Huriye Uzun (Bio-Protocol)
Flippases, a functionally distinct group of transmembrane proteins that flip lipids from the extracellular or luminal side to the cytosolic side of biological membranes, are key players in many important physiological processes, such as membrane trafficking and cellular signaling. To study the function of these membrane proteins under chemically defined conditions, reconstituting them into artificial vesicles is a crucial and effective approach. There are various methods for protein reconstitution involving different detergents and detergent removal techniques to integrate membrane proteins into artificial vesicles. In this protocol, we describe the reconstitution of the yeast flippase complex Drs2-Cdc50, which translocates phosphatidylserine across membranes of the trans-Golgi network at the expense of ATP hydrolysis. The flippase complex is incorporated into liposomes using a zwitterionic detergent, followed by detergent removal via dialysis—a gentle and effective strategy that helps preserve protein function. To evaluate the activity of the reconstituted flippase complex, two complementary assays are employed: (1) a fluorescence-based quenching assay to measure lipid transport; and (2) an ATPase assay using an ATP-regenerating system to measure ATP hydrolysis. Together, these methods provide a robust platform for analyzing the functional reconstitution of Drs2-Cdc50 in a defined membrane environment.